Constraining Cosmology with Secondary Anisotropies and Cluster Lensing of the Cosmic Microwave Background with the South Pole Telescope - Chaubal, Prakrut (2023)
© 2023 Prakrut Chaubal There is a wealth of information encoded in the higher angular multipoles of the Cosmic Microwave Background (CMB) waiting to be explored with high-resolution observations. In this thesis I will discuss the work done during my PhD, where I used the latest data, observed with the South Pole Telescope, to measure the secondary anisotropies of the CMB. I will also discuss the use of CMB-cluster lensing as a powerful tool to constrain cosmology. In this thesis, I present the first-ever measurement of the high-\el{} temperature anisotropies from the 2019-2020 winter observations of the 1500 \sqdeg{} SPT-3G survey. I discuss the method used to obtain an unbiased measurement of the bandpowers from the low level data from the telescope. Second, I investigate the lensing of the CMB by galaxy clusters. I show the improvement to cosmological constraints from galaxy cluster surveys with the addition of CMB-cluster lensing data. I explore the cosmological implications of adding mass information from the 3.1$σ$ detection of gravitational lensing of the cosmic microwave background (CMB) by galaxy clusters to the Sunyaev-Zel'dovich (SZ) selected galaxy cluster sample from the 2500 \sqdeg{} SPT-SZ survey and targeted optical and X-ray followup data. In the \lcdm{} model, the combination of the cluster sample with the Planck power spectrum measurements prefers $\sig(Ω_m/0.3)0.5=0.831±0.020$. Adding the cluster data reduces the uncertainty on this quantity by a factor of 1.4, which is unchanged whether or not the 3.1$σ$ CMB-cluster lensing measurement is included. We then forecast the impact of CMB-cluster lensing measurements with future cluster catalogs. Adding CMB-cluster lensing measurements to the SZ cluster catalog of the on-going SPT-3G survey is expected to improve the expected constraint on the dark energy equation of state w by a factor of 1.3 to $σ(w)$=0.19. We find the largest improvements from CMB-cluster lensing measurements to be for \sig, where adding CMB-cluster ...